Pendampingan Pembelajaran Berbasis Bermain melalui Media Balance and sort ball pada Anak Usia 4-5 Tahun - Putri Khaerunnisa; Ashar; Nurul Nisya; Yuniarti; Filayuliana; Arnitasari (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
Microteaching activities are an essential component of teacher professional education, aiming to develop the pedagogical, professional, social, and personal competencies of prospective teachers. One effective way to create meaningful learning experiences for early childhood students is through play-based learning that aligns with their developmental characteristics. This activity aimed to introduce different types of transportation (land, sea, and air), develop children's critical thinking, communication, and collaboration skills, and foster character values and gratitude among children aged 4-5 years. The learning process was carried out using a simple scientific approach through observing, discussing, experimenting, and reflecting with the support of the balance and sort ball media. Children observed pictures of vehicles, classified them based on their types, and participated in a paired game by carrying picture balls using chopsticks. Evaluation was conducted through observation using checklists and anecdotal notes to assess the achievement of learning objectives. The results showed that most developmental indicators were achieved, including cooperation, balance, vehicle classification and identification, and turn-taking during play. Therefore, play-based learning through the balance and sort ball media can serve as an effective alternative for promoting the holistic development of young children.